Relationship between pleural plaques and biomarkers of cumulative asbestos dose. A necropsy study - Barbieri, Pietro Gino; Consonni, Dario; Somigliana, Anna (La Medicina del Lavoro, 2019)
Background: The relationship between pleural plaques and cumulative asbestos exposure is controversial. Objectives: To evaluate the relationship between lung asbestos bodies (AB) and fibres (AF) and plaques presence and extension. Methods: In a necropsy series of shipyard workers with asbestos-related diseases, we measured counts (per g of dry lung tissue) of AB (thousands) and AF>1 µm (millions). Pleural plaques were classified into three extension grades. We fitted univariate and multivariable linear (dependent variables: AB and AF, log10 transformed) and multinomial (dependent variable: plaques grade) regression models. Results: We analysed 124 subjects, 13 without plaques 20 with grade 1, 69 with grade 2, and 22 with grade 3 plaques. Geometric means (GM) of AB were 10.6, 23.3, 126, and 140 in the four groups respectively (P=0.0001). GMs for AF (mostly amphiboles) were 1.2, 1.4, 7.3, and 12.9 (P=0.0001). AB and AF were strongly correlated (r=0.81). The likelihood of no plaques and grade 1 plaques decreased with increasing AB and AF doses, with a corresponding increase of grade 2 and 3 plaques. Plaque presence and extension was also associated with histologically verified asbestosis (P